Closure - Journal of Infrastructure & Facility Asset Management (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Journal of Infrastructure & Facility Asset ManagementVolume 4, Issue 1, April 2022 (e) ISSN 2656-8896 (P) ISSN 2656-890XJIFAM, Vol.4, Issue 2, August 2022Comparison of Embankment Reinforcement Requirements with Geotextile on Soft Soil with 2D and 3D Slope Stability Analysis Methods Nur Arfiati Shoffiana, Yudhi Lastiasih & Trihanyndio Rendy Satrya Evaluation of Smart Mobility Indicators in Responding COVID-19 Pandemic in Indonesia Shanty Y. Rachmat & Ganesha G. MangkoesoebrotoGeotechnical Mapping for Soil Physical and Mechanical Parameters and Hard Soil Depth in Badung Regency Zefira Wisna Maulidha, Trihanyndio Rendy Satrya & Yudhi Lastiasih Evaluating COVID-19 Transmission Prevention Measures in Public Rental Flats (Rusunawa) Rosyidah ‘Adilah, Prananda NavitasThe adequacy of Public Bus Fleet during the Covid-19 Pandemic (Case of The Transjakarta Corridor 1 DKI Jakarta, Indonesia) Amanda Dian W.Kusumawardani, Ibnu Syabri, Fika Novitasari & Naya C. Drestalita